Correlation between Lactic Acid Concentration and The Severity of Neonatal Sepsis - Iskandar, Agustin; Pranidya, Nada Putri; Sulistijono, Eko; Aryati, Aryati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
BackgroundsNeonatal sepsis remains a major cause of high infant mortality rate in Indonesia, and served as one of risk factor for early neonatal mortality. This study aims to determine the relationship between lactate levels andthe severity of sepsis and prognostic value of lactic acid as a predictor of severity in neonatal sepsis.. MethodsThis research is analytic observational research using cross sectional method. The subjects were patients of neonatal sepsis treated in the Perinatology Room of Saiful Anwar Hospital Malang from February to June 2015. Lactic acid concentration in plasma was measured by using enzymatic colorimetric  methodResults and DiscussionThe results showed a positive and significant correlation (p = 0,023; r= o,414) between lactate concentration and severity of sepsis, where every increase of sepsis degree increased lactate level of 0,151 mmol / L. Whereas by using  cut off ≥ 2.5 mmol / L, the prognostic test showed  66.7% of sensitivity and 76.2% of specificity. The chi square test of lactate> 2 mmol / L and <2 mmol / L showed Odd Ratio (OR) of 1,3 whereas at lactate level > 5 mmol / L and <5 mmol / L showed OR of 4,8 indicated that although there was no difference but the mortality outcomes of neonatal sepsis 4.8 times greater those of life. Thus lactate levelsof > 5 mmol / L can determine mortality outcome of neonatal sepsis.Conclusions and suggestionsThe higher the lactic acid level the more severe of neonatal sepsis. Lactate levels greater than 5 mmol / L was predictor for determining mortality outcome in neonatal sepsis